READING TUTORING FOR ELEMENTARY SCHOOL STUDENTS IN GOLO LANGKOK VILLAGE, RAHONG UTARA, MANGGARAI, EAST NUSA TENGGARA - Madu, Fransiska Jaiman (STKIP Santu Paulus Ruteng, 2019)
By reading a book, you can explore the world without leaving your seat. That was a glimpse of the saying that Plummer conveyed about the importance of reading. As an important matter, the ability to read is certainly a major demand for everyone, not least. Through reading, one can know many things like history, news, information, and so on. Reading is one of the basic competencies learned since elementary school. Children must learn to read from elementary school. However, what happens if there are still elementary school-age children who cannot read? This happens to children in Golo Langkok Village. There are still 17 children of primary school age who have not been able to read. These findings are considered a problem. Based on this problem, one solution is offered, namely the provision of tutoring for elementary school-age students who have difficulty reading in the village of Golo Langkok, Kecamatan Rahong Utara. The steps that will be carried out are: 1) analyzing the situation, 2) diagnosing, 3) activating children based on their abilities, 4) conducting reading learning activities. Based on the guidance activities carried out it can be concluded that children who experience reading difficulties need intense guidance. Learning outcomes after the guidance activities have been conducted show that students' reading ability increases. advanced reading difficulties